An agent-directed multisimulation framework for simulation games management. (1st January 2012) - Merkuryeva, Galina; Bikovska, Jana; Ören, Tuncer
The paper presents an overview of agent-directed applications in management of business simulation games. Functionality of agents and agent-based software platforms are analysed. The scenario-based game management concept is introduced in the paper. An agentdirected multisimulation framework for management of simulation games is proposed. An illustrative example for a specific web-based logistic simulation game is provided.